Statutory Rape And Juvenile Male Offenders: A Maqasid Al-shariah Analysis Of Rights And Legal Status In The Malaysian Legal System - Mohamad Aliyyuddin Mohd Nazir; Ahmad Ikmal Hishammudin; Muhammad Danish Idraak Muhamad Syazwan; Ahmad Amjad Ahmad Shafrin; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
This study offers a critical re-examination of Malaysia’s statutory rape laws, focusing on the unintended consequences for juvenile males prosecuted under Section 375(g) of the Penal Code. While these strict liability provisions are intended to safeguard minors from sexual exploitation, they often fail to distinguish between coercive abuse and consensual relationships among peers, resulting in the criminalisation of adolescent males who are themselves minors. Through a doctrinal and comparative legal analysis, the research highlights the dissonance between current punitive approaches and the principles of justice embedded in Maqasid al-Shariah, particularly ḥifẓ al-nasl (protection of lineage), ḥifẓ al-‘ird (protection of dignity), and al-‘adl (justice). The study further explores the inconsistencies arising from Malaysia’s dual legal system and contrasts these with close-inage exemptions applied in other jurisdictions, which offer a more balanced response. Findings reveal that the existing legal framework leads to significant psychological, social, and developmental harm for young offenders, exacerbating stigma and long-term disadvantage. The paper advocates for comprehensive reform, including introducing close-in-age exemptions, gender-neutral statutory provisions, and rehabilitative justice measures. By integrating Islamic ethical objectives, human rights norms, and contemporary insights into adolescent development, the study proposes a recalibrated approach that upholds child protection and equitable justice within Malaysia’s legal landscape.